+0  
 
0
33
1
avatar+50 

4cos(x)-4sin^2(x) + 5=0

x = ?

 
SurpriseMe  Jan 12, 2018

Best Answer 

 #1
avatar+5924 
+1

4cos x  -  4sin2x  +  5   =   0

                                                             From the Pythagorean identity,   sin2x   =   1 - cos2x

4cos x  -  4( 1 - cos2x )  +  5   =   0

                                                             Distribute the  -4  to both terms in parenthesees.

4cos x  -  4  +  4cos2x  +  5   =   0

                                                             Combine the  -4  and  +5   to get  +1 , and rearrange.

4cos2 x  +  4cos x  +  1   =   0

 

4( cos x )2  +  4( cos x )  +  1   =   0     This is a quadratic equation which factors like this...

 

4( cos x )2  +  2( cos x )  +  2( cos x )  +  1   =   0

 

2( cos x )( 2( cos x ) + 1 )  +  1( 2( cos x )  +  1 )   =   0

 

( 2( cos x )  +  1 )( 2( cos x )  +  1 )   =   0

 

( 2( cos x ) + 1 )2   =   0

                                          Take the square root of both sides.

2( cos x ) + 1   =   0

                                          Subtract  1  from both sides.

2( cos x )   =   -1

                                          Divide both sides by  2 .

cos x   =   -1/2

 

x   =   120°   +   360n°

 

x   =   240°   +   360n°       where  n  is an integer.

 
hectictar  Jan 12, 2018
Sort: 

1+0 Answers

 #1
avatar+5924 
+1
Best Answer

4cos x  -  4sin2x  +  5   =   0

                                                             From the Pythagorean identity,   sin2x   =   1 - cos2x

4cos x  -  4( 1 - cos2x )  +  5   =   0

                                                             Distribute the  -4  to both terms in parenthesees.

4cos x  -  4  +  4cos2x  +  5   =   0

                                                             Combine the  -4  and  +5   to get  +1 , and rearrange.

4cos2 x  +  4cos x  +  1   =   0

 

4( cos x )2  +  4( cos x )  +  1   =   0     This is a quadratic equation which factors like this...

 

4( cos x )2  +  2( cos x )  +  2( cos x )  +  1   =   0

 

2( cos x )( 2( cos x ) + 1 )  +  1( 2( cos x )  +  1 )   =   0

 

( 2( cos x )  +  1 )( 2( cos x )  +  1 )   =   0

 

( 2( cos x ) + 1 )2   =   0

                                          Take the square root of both sides.

2( cos x ) + 1   =   0

                                          Subtract  1  from both sides.

2( cos x )   =   -1

                                          Divide both sides by  2 .

cos x   =   -1/2

 

x   =   120°   +   360n°

 

x   =   240°   +   360n°       where  n  is an integer.

 
hectictar  Jan 12, 2018

19 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details